RHETORICAL FUNCTIONS OF METAPHORICAL LANGUAGE IN POLITICAL LEADERSHIP: XI JINPING AS A CASE STUDY - Xoliqova Zinora Abdurasulovna (Modern World Education: New Age Problems – New solutions, 2025)
This paper explores the rhetorical functions of metaphorical language in political leadership, using Xi Jinping’s speeches as a case study. Political leaders frequently use metaphor as a strategic tool to shape public opinion, reinforce ideology, and legitimize authority. Through qualitative analysis of selected speeches, the study reveals how Xi Jinping utilizes metaphorical language to construct political narratives, evoke cultural values, and guide national identity. The findings highlight the central role of metaphor in chinese political discourse and its effectiveness in leadership communication.